Replication of Scopolamine's Antidepressant Efficacy in Major Depressive Disorder: A Randomized, Placebo-Controlled Clinical Trial - Drevets, Wayne C.; Furey, Maura L. (Biological psychiatry (1969), 2010)
We previously reported that intravenous (IV) scopolamine administration produced rapid and robust antidepressant effects in a sample consisting of both unipolar and bipolar depressives. The present study aimed to replicate this finding in an independent sample limited to unipolar depressives. Outpatients with major depressive disorder (MDD; n = 23; 22 were included in analyses) participated in a double-blind, placebo-controlled, crossover trial. Subjects were randomized into either a P/S or S/P sequence (P = block of three placebo sessions; S = block of three scopolamine sessions; [4.0 μg/kg IV]). Sessions occurred 3 to 5 days apart, such that time spent in each block lasted 1.5 to 2 weeks and the interval between blocks was 3 to 5 days. The Montgomery-Asberg Depression Rating Scale (MADRS) served as the primary outcome measure. Following the initial block, the group receiving scopolamine first (S/P) showed a 32% reduction in MADRS scores ( p < .001), which exceeded the corresponding change of 6.5% under placebo (P/S; p = .009), confirming the a-priori hypothesis. Improvement was significant at the first evaluation that followed scopolamine administration ( p = .011). In Block 2, the P/S group showed a 53% reduction in MADRS scores ( p = .001) following scopolamine versus placebo, whereas the reduction seen in S/P subjects who received scopolamine during Block 1 persisted as they received placebo during Block 2. Scopolamine induced drowsiness, blurred vision, dry mouth, light-headedness, and reduced blood pressure, which were sufficiently well tolerated that no subject dropped out because of side effects. These results replicate previous finding that scopolamine produces a rapid and robust antidepressant response.